Malaysian orthopaedic surgeons' approach to venous thromboembolic disease prophylaxis: attitudes and practice. - Zairul-Nizam, Z.F.; Gul, Y.A. (SAGE Publications, 2003)
PURPOSE: To survey Malaysian orthopaedic surgeons' attitudes to and use of venous thromboembolic disease prophylaxis. METHODS: A total of 144 orthopaedic surgeons from various governmental and private institutions responded to a questionnaire. RESULTS: Only slightly more than half of these surgeons considered venous thromboembolic disease as common a problem in Malaysia as in western countries. The majority of surgeons (91.0%) reported using prophylaxis selectively for patients based on various indicators such as risk grading of surgery, obesity, and malignancy etc. Bleeding tendencies were cited as the greatest fear against the use of pharmacological prophylaxis. Low-molecular-weight heparin appeared to be the most commonly used pharmacological prophylaxis, used either singly or in combination with other forms of prophylaxis. The majority of surgeons employed prophylaxis until their patients were mobile. CONCLUSION: There should be greater awareness among surgeons in Malaysia of the need for protection against venous thromboembolic disease. Current practice needs to be reviewed and further recommendations made for existing protocols.